2009
DOI: 10.1007/s00442-009-1338-5
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungal species suppress inducible plant responses and alter defensive strategies following herbivory

Abstract: In a greenhouse experiment using Plantago lanceolata, plants grown with different arbuscular mycorrhizal (AM) fungal species differed in constitutive levels of chemical defense depending on the species of AM fungi with which they were associated. AM fungal inoculation also modified the induced chemical response following herbivory by the specialist lepidopoteran herbivore Junonia coenia, and fungal species varied in how they affected induced responses. On average, inoculation with AM fungi substantially reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 53 publications
5
102
2
1
Order By: Relevance
“…Increasingly, the importance of AMF for agricultural sustainability is being recognized (Sanders 2010;Verbruggen and Kiers 2010). Via various attributes, such as nutrient acquisition (Johnson 2010;Smith and Read 2008), pathogen suppression (Lendzemo et al 2005), herbivory protection (Bennett et al 2009;Gange and West 1994) and improved water relations and soil structure (Augé 2001;Wilson et al 2009), mycorrhizal fungi can benefit crop hosts and ecosystem sustainability. For example, recent studies have shown that AMF are fundamental in preventing nutrient loss in modelled grasslands after raininduced leaching events, resulting in an up to 60% reduction of phosphorus loss (Asghari et al 2005;van der Heijden 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, the importance of AMF for agricultural sustainability is being recognized (Sanders 2010;Verbruggen and Kiers 2010). Via various attributes, such as nutrient acquisition (Johnson 2010;Smith and Read 2008), pathogen suppression (Lendzemo et al 2005), herbivory protection (Bennett et al 2009;Gange and West 1994) and improved water relations and soil structure (Augé 2001;Wilson et al 2009), mycorrhizal fungi can benefit crop hosts and ecosystem sustainability. For example, recent studies have shown that AMF are fundamental in preventing nutrient loss in modelled grasslands after raininduced leaching events, resulting in an up to 60% reduction of phosphorus loss (Asghari et al 2005;van der Heijden 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bennett et al, 2006;Koricheva et al, 2009;Gange, 2007;Hartley and Gange, 2009). As known from insect herbivores (Bennett and Bever, 2007;Bennett et al, 2009), also the effects of AM on spider mite performance and plant response are highly variable and depend on the AM fungus species involved (Nishida et al, 2010). In an outdoor glass chamber experiment, Lotus japonicus (Regel) Larsen was inoculated with four different AM fungus species, namely Gigas- Compounds associated with induced resistance to herbivores in general and spider mites in particular were differentially altered, depending on the AM fungus species (Nishida et al, 2010).…”
Section: Spider Mites and Belowground Symbiontsmentioning
confidence: 99%
“…In tripartite interactions, the identity of all three interacting species is important and may influence the results of interactions (Bennett et al 2009;Kempel et al 2013;Zytynska et al 2014;Parker et al 2017). A recent study by Bonte et al (2010) found that spider mites adapted to the physiological change in snap beans induced by AMF in just fifteen generations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of symbiotic relationships on herbivores is not straightforward. For example, arbuscular mycorrhizal fungi (AMF) have been found to both induce and suppress herbivore defense in plants; the outcome appears to depend on the identity of all participants (Bennett et al 2009;Kempel et al 2013). White clover that was inoculated with rhizobia showed increased growth for both the plant and herbivore (Kempel et al 2009).…”
Section: Introductionmentioning
confidence: 99%